Determinasi Triple Bottom Line Disclosure Terhadap Nilai Perusahaan dengan Profitabilitas dan Volatilitas Arus Kas Sebagai Pemoderasi dan Ukuran Perusahaan Sebagai Variabel Kontrol - Sri Wahyuni; Sutan Febriansyah (Department of Accounting, Faculty of Economics & Business, 2023)
This study aims to examine the effect of The Triple Bottom Line (TBL) on firm value moderated by profitability and cash flow volatility. The two moderaing variables are controlled by firm size as a control variable. The sample was taken using a purposive sampling technique and the sample obtained was 43 companies that won Indonesia Corporate Social Responsibility Awards (ICSRA) 2021. This study used Moderated Regression Analysis (MRA). The result show that The Triple Bottom Line (TBL) and cash flow volatility have no effect on the value of the Indonesia Corporate Social Responsibility Awards (ICSRA) 2021. Meanwhile, profitability has a negative effect on firm value. In term of moderation, its is found that profitability is proven to be able to strengthen the relationship between the Triple Bottom Line (TBL) and firm value. Meanwhile, cash flow volatility was not able to strenghthen the relationship between the Triple Bottom Line (TBL) and firm value.